Exploring sustainability education : perspectives of Finnish pre-service teachers - Abitha Chakrapani (2023)
The study investigates sustainability education (SE) in the context of teacher education in Finland. It focuses specifically on pre-service teachers enrolled in teacher education programs at the University of Jyväskylä (JYU). The study explores how preservice teachers perceive sustainability and how teacher education programs could be strengthened to promote sustainability as a key component of pedagogy. Two research questions guided the study: 1) What is the understanding of sustainability education among Finnish pre-service teachers? 2) How is sustainability education embedded in the teacher education curriculum at JYU, and in what terms? Data for this study was collected through six (6) one-on-one interviews with pre-service teachers from different cohorts of the University of Jyväskylä's teacher education program and document analysis, including the 'Teacher Education Curriculum 2014–2017' and the 'JYU Teacher Training Values OPS 2020–23'. Thematic analysis was employed to analyze the interview data with the help of a qualitative data analysis tool, Atlas.ti. The findings showed that respondents hold different perspectives on the topic of sustainability education, with some focusing primarily on the environmental dimension. Other respondents expressed views on a social perspective. However, none of the respondents identified all four perspectives—economic, cultural, social, and environmental—coherently. The study also found that study programs on sustainability are few, with pedagogy and curriculum inadequate to prepare teachers for sustainability education. Respondents mentioned only three courses that address sustainability: KTKP020, Kasvatus, yhteiskunta ja muutos (education, society, and change); POMM 1093, ympäristö ja tiedekasvatus (environmental and science education); and POMMI 1043, Käsityökasvatus (handicraft and science). The findings suggest gaps in student teachers' awareness of sustainability, as well as a lack of courses explicitly focused on sustainability-related themes within the University of Jyväskylä's teacher education program. Thus, integrating sustainability courses into teacher education programs, with a special emphasis on educating prospective teachers with the knowledge and skills needed to create a sustainable future through education, is recommended.